KEWENANGAN MAHKAMAH KONSTITUSI DALAM PROSES IMPEACHMENT PRESIDEN MENURUT SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Fauzan, Muhammad (Jurnal Dinamika Hukum, 2011)
The authority of the Constitutional Court to adjudicate and decide upon the opinion of the House of Representatives that the President and/or vice  president has violated the law of treason to the state, corruption, bribery, other felonies, or moral turpitude, and/or that the President and /or Vice President no longer meets the conditions as President and/or Vice President are normative efforts to avoid a repeat of dismisal that are soley based on slander and suspicion which are only to satisfy the political interests of political elites. Key words : The authority of the Constitutional Court, Impeachment